Social representations on migration by female latin american immigrants in Valencia (Spain) - Moura, Giovanna (2019)
This study was developed under the focus of social psychology, aiming to understand the social representations of Latin American immigrant women from Argentina, Colombia, Brazil, Ecuador and Bolivia, who reside in Valencia, Spain about the constructs: “immigration”(1), “immigrants”(2), “Spanish”(3), “Valencia”(4) and “discrimination”(5). The sample was non-probabilistic and convenience, formed by 179 immigrants, between 18 and 59 years, which responded to the technique of free association of words. The results of the stimuli revealed that social representations about the immigration have been targeted as: money, interculturality, journey, knowledge and nostalgia; while on immigrants were: traveller, necessity, exit, knowledge. In relation to the stimulation induces Spaniards have the social representations: racist, evil, Crisis, friends, educated; the city of Valencia was represented as: beautiful, tourist, paella; already the stimulus discrimination was represented as: hatred, prejudice, maltreatment, racism, xenophobia, violence, fear, maltreatment and ignorant. The sample was non-probabilistic and convenience-wise, formed by 179 immigrants, aged between 18 and 59, who answered to the technique of free association of words. The results of the stimuli showed that the social representations about immigration were objectified as: money, interculturality, travel, knowledge and nostalgia; while on immigrants were: traveler, need, leave, knowledge. Regarding the Spaniards inductive stimulus we got the following social representations: racist, evil, crisis, friends, educated; the city of Valencia was represented as: beautiful, tourist, paella; as for the discrimination stimulus, we found: hatred, prejudice, mistreatment, racism, xenophobia, violence, fear and ignorance. The social representations have provided a better understanding about the activities affective, cognitive and symbolic of the participants in their everyday interactions and social positions. It is hoped that these findings will contribute to deepening the study and knowledge of female migration as well as provide changes that encourage integration, development and well-being of the population.